Achieving Integrated Government-to-Business Service Delivery : A Planning Guide for Reformers - World Bank (World Bank, Washington, DC, 2020)
Governments worldwide are designing and implementing new institutional and technology approaches for providing integrated government-to-business (G2B) services, recognizing the many benefits that can be realized both by government regulators and businesses. The outcomes that governments are seeking by implementing these integrated service delivery (ISD) approaches include: (i) better service, (ii) improved government efficiency, (iii) enhanced regulatory oversight and compliance, (iv) reduced opportunities for corruption, and (v) increased reach of service delivery across their jurisdictions. However, many countries have had to start the process from weak positions, as they cope with ministries and agencies operating in silos, aging and fragmented technology platforms, and lack of a service-oriented ethos. This guidance note draws on the experience of several countries that have implemented ISD solutions, and it aims to provide World Bank staff and client governments with a practical understanding of the concepts behind integrated service delivery and the reforms and investments required to implement it. A main objective of this note is to provide a planning framework that governments can use to comprehensively address the key institutional, governance, financial, and technology issues involved in ISD initiatives.